Prototype Of Chili Plant Pest Trap Using Arduino UNO - Khairunnazri, Khairunnazri; Fahrurrozi, Muh. (Jurnal Info Sains : Informatika dan Sains, 2024)
Chili farmers often experience losses due to pests which always damage chili plants. So that farmers can increase their production results, a solution is needed that can help farmers deal with this problem, namely by making a microcontroller-based pest trap Arduino Uno which is much more natural and safe than chemical pesticides, with a long usage period and the results are also much more promising. rather than using chemical pesticides. Arduino is used as a control center in the process of catching pests. As a control center, Arduino is installed with programming logic to be able to run other tools such as the HC-SR04 ultrasonic sensor as a pest detector, a relay as an extension of the ultrasonic sensor command to run a fan (fan cooler) to suck up pests, and a light sensor to turn on the attractant lights at night. days so that this pest trap protects chili plants for 24 hours.